Analysis of Biochar Adsorption of Heavy Metal Ions in Water - Zhang, Xuming (Exploring Science Academic Conference Series, 2026)
At present, heavy metal ion pollution in water bodies has become a major challenge in global water environment governance. Although conventional treatment technologies such as chemical precipitation, membrane separation, ion exchange, and electrochemical m ethods are widely applied, they are often constrained by high operational costs, secondary pollution risks, and complex processing procedures. Against this background, biochar has attracted increasing attention as a promising material for water pollution remediation. This paper compares the physicochemical differences between plant -based biochar and solid waste-based biochar, with a focus on their implications for adsorption performance in different environmental conditions. The results indicate that the adsorption of heavy metal ions by biochar is governed by the combined effects of physical adsorption, chemical interactions, and ion exchange processes. These mechanisms together provide a more integrated explanation of the adsorption behavior of biochar in aquatic environments.